A Treatise of Legal Philosophy and General Jurisprudence
XXII, 740 p.
Keywords: TO VOLUMES 9 AND 10 OF THE TREATISE I am happy to present here the third batch of volumes for the Treatise project: This is the batch consisting of Volumes 9 and 10, namely, A History of the P- losophy of Law in the Civil Law World, 1600–1900, edited by Damiano Canale, Paolo Grossi, and Hasso Hofmann, and The Philosophers’ Philosophy of Law from the Seventeenth Century to Our Days, by Patrick Riley. Three v- umes will follow: Two are devoted to the philosophy of law in the 20th c- tury, and the third one will be the index for the entire Treatise, which will 1 therefore ultimately comprise thirteen volumes. This Volume 9 runs parallel to Volume 8, A History of the Philosophy of Law in the Common Law World, 1600–1900, by Michael Lobban, published in 2007. Volume 10, for its part, takes up where Volume 6 left off: which appeared under the title A History of the Philosophy of Law from the Ancient Greeks to the Scholastics (edited by Fred Miller Jr. in association with Carrie-Ann Biondi, likewise published in 2007), and which is mainly a history of the p- losophers’ philosophy of law (let us refer to this philosophy as A).